(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
Analysis of the essence and application processes of pre-article printing process systems; optimization of technological factors of pre-click processes; analysis of the quality indicators of the copies obtained on different printing papers by applying a printing mold to different CTP equipment and the methods of evaluating exactly the color blinds from them, as well as the technological processes that affect them; study of technological factors affecting product quality in CTP equipment in the preclick process; it consists in a comparative analysis of the quality parameters of the products obtained in their pre-printing processes and an assessment of the quality of the printed product.